2018
DOI: 10.1007/s00464-018-6083-6
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic total extraperitoneal hernia repair under regional anesthesia: a systematic review of the literature

Abstract: Spinal anesthesia for total extraperitoneal inguinal hernia repair seems safe and feasible. However, more well-designed randomized clinical studies are required to determine the safety as well as the advantages and disadvantages of regional anesthesia in TEP hernia repair in different population groups before this method can be adopted into routine daily clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
26
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(32 citation statements)
references
References 48 publications
3
26
3
Order By: Relevance
“…In 3 metaanalysis studies, the risk of having headache was found to be higher in the SA group compared with the GA group. 7,8,21,23 In our study, significantly higher rates of headaches were detected in EA (6.8%) and SA (11.4%) groups compared with GA (0%) groups. In 2 meta-analyses, the incidence of urinary retention was higher in SA compared with GA. 8,23 In the study comparing EA and GA, 24 urinary retention was detected in 1 patient (3.3%) in the EA group, but there was no significant difference between the 2 groups.…”
Section: Discussionsupporting
confidence: 49%
See 2 more Smart Citations
“…In 3 metaanalysis studies, the risk of having headache was found to be higher in the SA group compared with the GA group. 7,8,21,23 In our study, significantly higher rates of headaches were detected in EA (6.8%) and SA (11.4%) groups compared with GA (0%) groups. In 2 meta-analyses, the incidence of urinary retention was higher in SA compared with GA. 8,23 In the study comparing EA and GA, 24 urinary retention was detected in 1 patient (3.3%) in the EA group, but there was no significant difference between the 2 groups.…”
Section: Discussionsupporting
confidence: 49%
“…In the literature, to prevent hypotension, it is recommended to hydrate patients before surgery, establishing pneumoperitoneum at lower pressures, tilting the operating table, and finally administering appropriate medication. 7 During our study, most of the hypotension complaints observed in the patients were corrected with intravenous fluid given during surgery. In a small number of patients, their hypotension improved without any additional intervention in clinical follow-up.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…The latter has been also confirmed in a previous study from our group, where 32% of patients under spinal anesthesia developed POUR [4]. However, despite these, spinal anesthesia, still, remains an attractive option for IH repair [5], since regional anesthesia is associated with favorable results in terms of hypotension, postoperative nausea, vomiting, and pain [3,6].…”
Section: Introductionsupporting
confidence: 82%
“…Meantime, TEP is less influenced by intraabdominal conditions because the procedure avoids entering into peritoneal cavity, such as peritoneal adhesion. [2022] But TEP may be associated with a high risk of extraperitoneal hematoma, collections in the Retzius space. In this retrospective study, all TEP repair was successfully performed and without conversion to TAPP or open repair, but peritoneum rupture occurred in 4 patients.…”
Section: Discussionmentioning
confidence: 99%